2018
DOI: 10.1038/s41533-018-0081-y
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent lower respiratory illnesses among young children in rural Kyrgyzstan: overuse of antibiotics and possible under-diagnosis of asthma. A qualitative FRESH AIR study

Abstract: Lower respiratory tract illnesses (LRT-illnesses) in children under 5 years (U5s) are a leading cause of morbidity, hospitalisations and mortality worldwide, particularly in low-income countries. It is pertinent to understand possible inconsistent management. This study explored perceptions and practices among caregivers and health professionals on recurrent LRT-illnesses in U5s. Semi-structured interviews with 13 caregivers to U5s with recurrent LRT-illnesses and with 22 primary care health professional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…[2][3][4]7,[20][21][22][25][26][27] In this study, 41.5% of infants with recurrent asthma-like symptoms whose parents also reported severe episode and visit ED have not received ICS; similar percentages have been found in previous studies. 21,22,27 According to major guidelines, ICS therapy in preschool children with high risk for asthma is an effective approach for preventing exacerbations and symptom reduction. 27 Recently, in a large sample of infants with asthma-like symptoms, there was a significant reduction in the rate of admission for wheezing after starting with controller therapy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…[2][3][4]7,[20][21][22][25][26][27] In this study, 41.5% of infants with recurrent asthma-like symptoms whose parents also reported severe episode and visit ED have not received ICS; similar percentages have been found in previous studies. 21,22,27 According to major guidelines, ICS therapy in preschool children with high risk for asthma is an effective approach for preventing exacerbations and symptom reduction. 27 Recently, in a large sample of infants with asthma-like symptoms, there was a significant reduction in the rate of admission for wheezing after starting with controller therapy.…”
Section: Discussionsupporting
confidence: 88%
“…2 The authors identified a strong association between the severity of recurrent asthma-like symptoms and admission to hospital for wheezing, suggesting the need to improve the symptoms' severity recognition and medical management because this might prevent visits to ED and admissions in this group of infants, particularly in developing countries. 3,4,6,[19][20][21][22][23][24] In infants with troublesome recurrent asthma-like symptoms and older asthmatic children, there are several treatment-related issues: repeated use of antibiotics, poor inhalation technique and treatment adherence, ICS at low doses, discontinuous use of ICS, among others, will predictably result in poor treatment outcomes. [2][3][4]7,[20][21][22][25][26][27] In this study, 41.5% of infants with recurrent asthma-like symptoms whose parents also reported severe episode and visit ED have not received ICS; similar percentages have been found in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) The diagnosis and treatment of asthma in children should be tailored as if infectious disease is highly prevalent, asthma is often unknown to healthcare workers and its diagnosis is regularly missed [23,24].…”
Section: Reducing Household Air Pollution Exposure and Improving The Diagnosis And Treatment Of Lung Diseasesmentioning
confidence: 99%
“…Overuse of antibiotics in children has been reported in both high-income 4 and low-income countries. 5 Other examples of inappropriate use of medicines are the widespread use of cough medicines in children 6 and polypharmacy. 7 Polypharmacy is associated with an increased risk of drug toxicity.…”
mentioning
confidence: 99%